Oral lichen planus: A retrospective study of 110 Brazilian patients - Oliveira Alves, Mǒnica Ghislaine [UNESP]; Almeida, Janete Dias [UNESP]; Balducci, Ivan [UNESP]; Guimar̃es Cabral, Luiz Antonio [UNESP] (Springer Nature, 2010)
Background. Oral lichen planus (OLP) is a chronic autoimmune disease characterized by multiple clinical presentations and a relatively high prevalence in the population. This retrospective patient record study investigated the profile of OLP in a group of Brazilian patients seen between 1989 and 2009. Findings. The clinical records were analyzed and data such as gender, age, race, clinical presentation of OLP, site affected, presence of symptoms and extraoral manifestations of the disease, smoking habit, and consumption of alcoholic beverages were obtained. Among the 1822 records of patients with oral mucosal lesions, OLP was identified in 6.03%. Of these, 76.36% were females, with a mean age of 54 years, and 85% were whites. The reticular form was the most frequent (81.81%). Extraoral lesions were observed in 32.72% of the patients and painful symptoms were reported by 50.90%. The cheek mucosa was the site most affected (92.72%) and multiple oral lesions were observed in 77.27% of the patients. Among patients with OLP, 18.18% reported a smoking habit and 29.09% the consumption of alcoholic beverages. Conclusions. This retrospective study showed a relatively high prevalence of OLP in the population studied, with a predominance of the disease among middle-aged white women and bilateral involvement of the cheek mucosa. Reticular lesions were the most frequent, followed by the erosive form which is mainly associated with painful symptoms. No relationship with tobacco or alcohol consumption was observed. © 2010 Almeida et al; licensee BioMed Central Ltd.
Keywords: Nicotiana tabacum